Ligature-induced periodontitis in rats and mice: a systematic review on therapeutic targets / Noor Azliza Wani Abd. Aziz ... [et al.] - Abd. Aziz, Noor Azliza Wani; Zainal Ariffin, Muhammad Hilmi; Mhd Zukhi, Aina Athirah; Din, Nur Sarah Izzati (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Periodontitis is currently managed through plague removal, both mechanically and chemically. However, limitation to reach the base of deep pockets often results in incomplete protection from periodontal pathogens. Therefore, new treatment modalities are emerging with the aim of controlling the inflammationassociated surrounding tissue damage. There have been strong evidences of preclinical studies on the mechanisms of protection, which may bring insights into the potential therapeutic target(s). We performed a systematic review to identify the therapeutic target(s) in rodent model of periodontitis. Method: The study protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO), ID: CRD42022355578. We searched PubMed, Scopus, and Wiley databases from 2017 to 2021. This systematic review was conducted in accordance with the PRISMA guidelines and studies were selected based on predefined inclusion criteria. We developed a diagram to show the cellular location of the targets. These targets were summarized based on their effects on the outcome determinants such as inflammatory response and the extend of alveolar bone and/or periodontal attachment loss. Decision matrix analysis was used to identify which target(s) hold the most potential. Result: Eleven studies met the inclusion criteria. Result showed that protection in early and late phases of periodontitis involve targets such as transcription factor, protein and lipid kinases, transmembrane receptor, and extracellular protein. Further analysis showed that transcription factor is the most investigated target with the most reported protective outcomes. Conclusion: Protective targets in periodontitis involve different cellular levels. Transcription factor appears as the most potential therapeutic target in rodent model of periodontitis.